The Effectiveness Of The Communicative Method In Teaching German In Higher Education - Ruzieva, Mahbuba (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the use of the communicative method in teaching German in higher education institutions and its effectiveness. The study is aimed at studying the importance of the communicative approach in the methodology of modern foreign language teaching, its theoretical foundations and practical application.